Challenging ideas : theory and empirical research in the social sciences and humanities - Lytje, Maren; Nielsen, Torben K.; Jørgensen, Martin Ottovay (Cambridge Scholars Publishing, 2015)
Challenging Ideas is a selection of articles which address the intersections between theory and empirical research. In general, the contributions to the volume focus on how imaginations of the temporal relationship between past and present might inform theory as well as empirical research. It is divided into two parts, the first of which, Memory, looks at the memory turn in the discipline of history, and includes investigations into the relationship between past and present in the working through of trauma and reflections on the relationship between media memory, collective memory and trauma.